Recognition of a likely two phased extinction at the K-Pg boundary in Antarctica. Issue 1 (December 2017) - Tobin, Thomas
Abstract The southernmost Cretaceous – Paleogene (K-Pg) outcrop exposure is the well-studied exposure on Seymour Island, Antarctica. Deposition across the K-Pg boundary there is uninterrupted, and as a consequence the ammonite fossil record is commonly used to test statistical methods of evaluating mass extinctions to account for the incompleteness of the fossil record. Numerous detailed fossil data sets from Seymour Island, comprised dominantly of mollusks, have been published over the last 30 years, but in most cases have not received statistical treatment. Here a previously published statistical technique is modified, automated, and applied to all published macrofossil data sets available from Seymour Island. All data sets reveal likely evidence of two separate multi-species extinctions, one synchronous with bolide impact evidence at the K-Pg boundary, and another 45 ± 15 meters (~140–290 ky) below the boundary. The apparent earlier extinction primarily affects benthic mollusks, while the boundary extinction primarily affects ammonites. While there is no unique sedimentological change over the interval where the earlier extinction is identified, it is impossible to exclude the possibility that this pattern is stratigraphically controlled. The automation of this technique allows it to be applied easily to other large fossil data sets.